Relationship between the self-efficacy and the stages of the decision-making process: analysis of the future managers' perception - Karpinski, Atais Catarina; Cogo, Dieli Cristina; Antonelli, Ricardo Adriano; Meurer, Alison Martins (Revista de Administração da UFSM, 2020)
Purpose – This study analyzes the relationship between self-efficacy and the stages of the decision-making process, based on the perception of the undergraduate students in bachelor degree in Business Administration. Design/methodology/approach – It characterizes as a descriptive research, with a quantitative approach, using the Structural Equation Modeling technique, and data collection performed through a survey. Findings – The results indicate an association between self-efficacy and the stages of the decision-making process, allowing partial acceptance of the research hypothesis. In this sense, Effectiveness towards Adversity and Social Efficacy are shown as elements to be observed in terms of developing skills, which enable the students to realize such constructs, since there is a significant relationship with behavior in the decision making process. Thus, self-efficacy is presented as a propeller of the individual's confidence in the challenges and experiences with interpersonal relationships, whose experience supports the cognitive process which enables the recognition of the situation and the actions to be developed. Moreover, it is worth noticing the relevance of considering behavioral aspects in decision-making studies; regarding to, as well, the current discussions about the limitations of rational decision models. Research limitations/implications – The cross-section time frame and the sample composition of academics at a university are limitations that can be overcome in the future. Originality/value - Analyzing the relationship of self-efficacy with the stages of the decision-making process becomes relevant, since it brings contributions on the relationship of subjective abilities with decision making, in order to highlight characteristics not covered by rational decision-making models.